Pengaruh Senam Vertigo (Canalit Reposition Treatment) Terhadap Keseimbangan Tubuh Pada Pasien Vertigo - Eni Sumarliyah; Suyatno Hadi Saputro (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
This study aims to analyze the effect of vertigo (canalit reposition treatment) exercise on body balance in vertigo patients and treatments. The specific purpose of this research is to identify the balance of the body in the control group and the design in this study is a Quasy Experimental study using a Static Group Comparison / Non Exuivalent Group Design research design approach. The hallmark of this research is revealing a causal relationship by looking at one treatment group compared to the control group. The treatment group was observed body balance before vertigo gymnastic intervention (canalit reposition treatment), then observed again after vertigo gymnastic intervention (canalit reposition treatment), while the control group only observed body balance without giving treatment. The population in this study were patients who were hospitalized with simple random sampling technique. Data collection was carried out through questionnaires and observations, then the data was processed and analyzed using the Wilcox statistical test with α 0.05.Based on the results of research that has been done obtained from the Wilcoxon test in the treatment group obtained α = 0,000. While from the control group, the result α = 0.003 This means that there is an influence between Vertigo Gymnastics (Canalit Reposition Treatment) on Body Balance in Vertigo Patients. However, there were differences between the treatment and control groups. Based on these results, the Vertigo Gymnastics (Canalit Reposition Treatment) affects the body’s balance in Vertigo patients.We are confident that Vertigo Gymnastics (Canalite Reposition Treatment) can be used in Vertigo patients in dealing with disorders of body balance as a companion therapy in addition to pharmacological therapy. With Vertigo Gymnastics (Canalite Reposition Treatment), balance disorders can be resolved immediately and the problem of comfort disorders in patients will be resolved as soon as possible.